2021
DOI: 10.1039/d1cc01451j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical nitrogen reduction: recent progress and prospects

Abstract: Ammonia is one of the most useful chemicals for the fertilizer industry and is also promising as an important energy carrier for fuel cell application, which is currently and mostly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 159 publications
0
78
0
Order By: Relevance
“… From Figure b, N 2 H 4 concentration is negligible after 2 h ENRR at the six potentials tested, confirming the selectivity of 6Cu–ZrO 2 for converting N 2 to NH 3 . Additionally, it is necessary to further identify the source of ammonia using 15 N isotopic labeling experiment. , After the electrochemical testing using 15 N 2 and 14 N 2 gas as the N source, respectively, 14 NH 4 + and 15 NH 4 + were detected in 1 H NMR spectra (Figure c), which indicates that the reduction of N 2 is the sole origin for ammonia production in this study. The UV–vis absorption spectra of the electrolytic process alternatively aerating N 2 and Ar for every 2 h show steady ups and downs in Figure S10.…”
Section: Resultsmentioning
confidence: 75%
“… From Figure b, N 2 H 4 concentration is negligible after 2 h ENRR at the six potentials tested, confirming the selectivity of 6Cu–ZrO 2 for converting N 2 to NH 3 . Additionally, it is necessary to further identify the source of ammonia using 15 N isotopic labeling experiment. , After the electrochemical testing using 15 N 2 and 14 N 2 gas as the N source, respectively, 14 NH 4 + and 15 NH 4 + were detected in 1 H NMR spectra (Figure c), which indicates that the reduction of N 2 is the sole origin for ammonia production in this study. The UV–vis absorption spectra of the electrolytic process alternatively aerating N 2 and Ar for every 2 h show steady ups and downs in Figure S10.…”
Section: Resultsmentioning
confidence: 75%
“…The advantages and shortcomings of these methods can be clearly visualized in Table 3; accordingly, it is necessary to choose these methods reasonably. 19,162–166 Only recently, after a detailed analysis of these detection methods, Zhao et al 167 found that if these methods are used in combination, the detection of low NH 3 content in the solution can be solved. The accurate detection of the total production of NH 3 can be achieved at extremely low concentrations (lower than 1 ppm or even 0.2 ppm) according to their reports.…”
Section: Applications Of Mos2-based Materials In Nrr Activitymentioning
confidence: 99%
“…16 Recently, electrochemical nitrogen (N 2 ) fixation by using water as the proton source has emerged as a highly appealing alternative to the Haber–Bosch process for ambient and green NH 3 synthesis. 17–21 Except for the electrocatalytic water splitting and N 2 fixation, carbon dioxide (CO 2 ) electroreduction proceeds via multi-electron (even twelve-electron) reduction pathways and generates more products, 22–29 offering a clean and promising approach for generating fuels such as CH 4 and C 2 H 5 OH under mild conditions. Thus, it is highly desirable to reduce the unsustainable consumption of fossil fuels via the conversion of gaseous feeds (such as H 2 , N 2 , and CO 2 ) into fuels and other value-added products using renewable electricity.…”
Section: Introductionmentioning
confidence: 99%
“…3 Electrocatalytic nitrogen reduction has emerged as a promising alternative and attracted intensive research attention. [4][5][6][7][8][9][10][11][12][13] However, its faradaic efficiency (FE) and NH 3 yield are both extremely hampered owing to (1) the strong NRN triple bond (941 kJ mol À1 ), (2) the low solubility of nitrogen in water, and (3) the competitive hydrogen evolution reaction (HER). Compared with nitrogen, nitrate (NO 3 1 ) is advantageous because of…”
mentioning
confidence: 99%